Mechanical Uniaxial Tensile Performance of Hybrid Glass/Carbon Woven Composites - Mohd Zulkifli, Muhammad Nasrun Faris; Yahya, Mohamad Faizul (International Journal of Integrated Engineering, 2024)
Carbon fibres are widely recognized for their remarkable strength-to-weight ratio, but their high cost and limited lifespan have prompted researchers to explore alternative materials. One promising solution is the use of hybrid composites, which combine carbon fibres with other fibre types, to maintain mechanical strength at optimal levels while reducing costs. A scientific study was conducted to investigate the impact of stacking configuration on hybrid glass/carbon woven composites. The study established eight stacking configurations based on the incorporation of identical and non-identical weave structures at the outermost layers. The hybrid glass/carbon woven composites were fabricated using the hand lay-up approach, with epoxy resin used as the polymer matrix. The results of the study showed that the hybrid B configuration yielded the highest tensile strength at 322.75 MPa, while the hybrid F sequence generated the lowest tensile strength at 169.00 MPa. The findings from this study indicated that the incorporation of weave structures with longer yarn floats in a non-identical arrangement at the outermost layer resulted in improved uniaxial tensile strength performance.